Increase in disturbance-induced canopy gaps leads to reorganization of Central European bird communities - Anne Graser; Claudia Frank; Friederike Kunz; Andreas Schuldt; Cornelius Senf; Christoph Sudfeldt; Sven Trautmann; Johannes Kamp (Basic and Applied Ecology)
Natural and anthropogenic forest disturbances have profound impacts on biodiversity and habitats. Due to climate change and land-use legacies, natural disturbances in Central European forests – such as windthrow and insect outbreaks – have increased in recent decades. How those changes affect biodiversity has, however, rarely been quantified over larger spatial and longer temporal scales, mostly because concurrent datasets on biodiversity trends and forest disturbances are rare. Here, we investigate the effect of canopy gaps resulting from both natural and anthropogenic forest disturbance on bird species. We harnessed a unique dataset from a nation-wide bird monitoring scheme containing richness and abundance data from 927 plots monitored annually from 2005 to 2019 across all of Germany (153,014 observations). We related bird richness and abundance to disturbance (measured as the disturbance fraction, i.e. canopy gap area in relation to the total forest area per monitoring plot) derived from a 30 m-resolution forest disturbance layer based on Landsat satellite data. This allowed us to assess effects of young canopy gaps (disturbance <5 years ago) and older canopy gaps (disturbance 5–10 years ago) on population trends of single species, combined trends across functional groups and bird diversity. Responses to disturbance were largely species- and trait-specific, with contrasting effects of different canopy gap age not necessarily accompanied by a change in overall bird diversity. Abundance trends of forest birds as well as short-distant migrants were negatively affected by young canopy gaps. Older canopy gaps led to more positive trends in shrub-nesting birds and short-distant migrants. We conclude that the recent increase in disturbance-induced canopy gaps across Central Europe has led to community reorganization, including species-specific changes in abundances. These changes might have important implications for priority-setting in species conservation.